A cross-sectional study comparing predictors of non-suicidal self-injury among college students in the United States and Greece. Issue 1 (2nd January 2017) - Kokaliari, Efrosini D.; Roy, Ann W.; Koutra, Kleio
ABSTRACT: The purpose of this study was to examine predictors of non-suicidal-self-injury (NSSI) including depression, stress, anxiety and suicidal behaviors (SIB) among students at two colleges in the USA and Greece. A convenience sample ( N  = 1062) was used along with the NSSI-Check List, SITBI, and DASS instruments. Significantly Greek (27%) reported higher rates of NSSI ( p < .01) versus the United States students (17%). Greek students engaged in self-biting, carving, and insertion of glass objects ( p  < .01) at a higher rate than the USA students. A model to predict NSSI revealed Greek students who reported an absence of suicidal thoughts, being heterosexual, Christian, and under stress, were 76% more likely to engage in NSSI ( p   <   .01). The USA students who reported an absence of suicidal thoughts and the presence of anxiety were 85% more likely to engage in NSSI ( p  < .01). Findings support the view that NSSI is a distinct phenomenon not necessarily related to suicidal behaviors and consistent with the NSSI diagnosis under further study (DSM-2013). As well, the high rates of NSSI along with depression, anxiety, and stress found in this study supports the literature urging NSSI be treated as a significant mental health issue.